Membrane Lipids in the Thyroid Comparing to Those in Non-Endocrine Tissues Are Less Sensitive to Pro-Oxidative Effects of Fenton Reaction Substrates - Stępniak, Jan; Rynkowska, Aleksandra; Karbownik-Lewińska, Małgorzata (Frontiers in Molecular Biosciences, 2022)
Iron is an essential microelement for the proper functioning of many organs, among others it is required for thyroid hormone synthesis. However, its overload contributes to the increased formation of reactive oxygen species via Fenton chemistry (Fe2++H2O2→Fe3++●OH+OH-) and it is potentially toxic. Individual organs/tissues are affected differently by iron excess. Excessive absorption of iron with subsequent deposition in various organs is associated with diseases such as haemochromatosis. Such an iron deposition also occurs in the thyroid gland where it can disturb thyroid hormone synthesis. In turn, melatonin is an effective antioxidant, which protects against oxidative damage. This study aims to check if lipid peroxidation (LPO), resulting from oxidative damage to membrane lipids, caused by Fenton reaction substrates, and if protective effects of melatonin differ between the thyroid and various non-endocrine porcine tissues (liver, kidney, brain cortex, spleen, and small intestine). To mimic conditions of iron overload, Fe2+ was used in extremely high concentrations. Homogenates of individual tissues were incubated together with Fenton reaction substrates, i.e. FeSO4 (9.375, 18.75, 37.5, 75, 150, 300, 600, 1200, 1800, 2100, 2400, 3000, 3600, 4200, 4800 µM)+H2O2 (5 mM), either without or with melatonin (5 mM). The concentration of malondialdehyde+4-hydroxyalkenals (MDA+4-HDA), as LPO index, was evaluated by spectrophotometrical method. Fenton reaction substrates increased concentrations of LPO products in all chosen tissues. However, in the thyroid, comparing to non-endocrine tissues, the damaging effect was generally weaker, it was not observed for two lowest concentrations of iron, and the LPO peak occurred with higher concentrations of iron. Melatonin reduced experimentally-induced LPO in all examined tissues (without differences between them) and these protective effects did not depend on iron concentration. In conclusion, membrane lipids in the thyroid comparing to non-endocrine tissues are less sensitive to pro-oxidative effects of Fenton reaction substrates, without differences regarding protective effects of melatonin.